Interpretation of Consulting Version in Islamic Study With Sociological Analysis: a Study of Thematic Interpretation - Fitriani Fitriani; Ecep Ismail (Gunung Djati Conference Series, 2021)
This study aims to discuss the interpretation of verses about deliberation in Islamic studies using sociological analysis. This research method uses a type of qualitative through the library research, which is a search for scientific knowledge from past and present scholars, using the thematic interpretation method, which is a process of collecting verses related to the theme of deliberation in the Al-Qur’an. As for sosiological analysis is used to study the sosial structure that occurs in society. The results and discussion of this study show that that the interpretation of deliberation in (Q.S Al-Baqarah (2) : 233, Q.S Ali Imran (3) : 159, and Q.S Asy-Syura (42) : 38) has a variety of interpretations. This is in accordance with the variety of words used, also based on the social consitions at the time the verses were revealed. This research concludes that in these three verses, Allah SWT. provide an affirmation, either spesific or general. Such as public affairs in the election of leaders, making plans and policies, as well as the appointment of state officials. If all of this carried out through a deliberation process, it will bring benefits to the people to bring embed, solidarity, and tolerance among others.